2019
DOI: 10.1039/c9na00305c
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced photocatalysis and bacterial inhibition in Nb2O5via versatile doping with metals (Sr, Y, Zr, and Ag): a critical assessment

Abstract: Enhanced photoactivity in Nb2O5 on incorporation of metal dopants towards degradation of water pollutants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 68 publications
(87 reference statements)
1
27
0
1
Order By: Relevance
“…[82,85j] Besides, the concentration of oxygen va-cancies can be increased when Nb 2 O 5 catalysts were doped with N, Zr, Y, Zn, or Mo species. [77,90,184] These phenomena were also observed on other metal oxides, like Cu-CeO 2 . [250] As a result, the photocurrent density of N-Nb 2 O 5 was higher than that of the pristine one.…”
Section: The Role Of Dopant and Surface Metal Speciesmentioning
confidence: 77%
See 1 more Smart Citation
“…[82,85j] Besides, the concentration of oxygen va-cancies can be increased when Nb 2 O 5 catalysts were doped with N, Zr, Y, Zn, or Mo species. [77,90,184] These phenomena were also observed on other metal oxides, like Cu-CeO 2 . [250] As a result, the photocurrent density of N-Nb 2 O 5 was higher than that of the pristine one.…”
Section: The Role Of Dopant and Surface Metal Speciesmentioning
confidence: 77%
“…[ 76 ] The additives, such as urea and melamine, acted as the fuel and template to fabricate TT‐Nb 2 O 5 particles in the calcination process. [ 12b,77 ] Furthermore, the as‐synthesized H‐Nb 2 O 5 particles can be treated under laser pulses to prepare amorphous Nb 2 O 5 , T‐Nb 2 O 5 , and TT‐Nb 2 O 5 , realizing the reversible transformation of crystal structures. [ 78 ]…”
Section: Synthesis Of Nb2o5‐based Photocatalystsmentioning
confidence: 99%
“…2e showed that the O 1s core-level spectra tted well to three peaks at the binding energies of 530.4, 532.0 and 533.3 eV, which were related to the Nb-O bond in Nb 2 O 5 , the Ag-O bond in Ag 2 O and the O-H bond of surface-absorbed water, respectively. 20,44,45 SEM was used to investigate the morphology of the resulting samples. Fig.…”
Section: Structure and Morphologymentioning
confidence: 99%
“…7,8 In this regard, many promising methods including metal and nonmetal doping, noble metal deposition or compositing with other semiconductor have been developed to improve the efficiency of Nb 2 O 5 as a photocatalytic material. [9][10][11][12][13][14][15] It has been proved that metal element doping was one of the most effective approaches to extend the spectral response of the wide-bandgap semiconductor to visible-light region. [16][17][18] Recently, some metal elements such as W, Mo, Fe, Cu and Mn have been employed to tune the electronic structure and enhanced the photocatalytic activity of the semiconductor photocatalysts.…”
Section: Introductionmentioning
confidence: 99%